Cultural space and communication production at mount Kelud, Indonesia - Wahyudi, Agus; Marijan, Kacung; Aminah, Siti (Faculty of Communications Science, Dr. Soetomo University, 2020)
The research aimed to understand the process of political communication in the contestation of Mount Kelud between the Blitar and the Kediri Regency Government in regional autonomy era. Mediation and legal efforts have been carried out to resolve Mount Kelud dispute, but the Central Government has not decided the administrative boundaries of the two Regencies since 2003. The research took the perspective of Henri Lefebvre's space production, which stated that space produced in the communityâ€™s daily life (social space) and produced by power (political space). The study used a qualitative method with a phenomenological approach. The findings of the study revealed that the Kediri Regency Government has carried out cultural construction and communication through the â€œLarung Sesajiâ€ in Kelud Mountain Festival. Meanwhile, Blitar Regency has not done similar activity; even if it has conducted the Sesani â€œLarung Intan.â€ The central government could consider the cultural space on Mount Kelud as a synthesis of social space and political space as an effort to resolve disputes over regional boundaries.